Economic Analysis of the Combined Heating System of Solar Collector and Gas Boiler. Issue 1 (July 2020) - Zhou, Hengchao; Li, Guangpeng
Abstract: The combined heating system of solar energy and gas-fired boiler is designed, the mathematical model of comprehensive heating cost is established, the suitable solar collector area is determined, three typical operating conditions of complex heating system are analyzed, and the consumption of various heating fuels is discussed. The results show that the efficiency of condensing boiler is more than 15% higher than that of non-condensing boiler.The combination of solar heating and gas-fired boiler has the most energy-saving heating effect, which can save more than 50% fuel compared with the boiler running alone.